Kajian Yuridis Kasus Pencurian Hasil Perkebunan di Jorong Kampung Pinang Ditinjau dari Hukum Positif dan Hukum Pidana Islam - Martaon Martaon; Fauzan Fauzan (AHKAM, 2026)
The increasing number of cases of theft of community plantation products in Jorong Kampung Pinang indicates a legal problem in handling theft crimes at the local level, particularly when cases are returned by the police to the community to be resolved amicably. This study aims to analyze the legal regulation of plantation product theft based on the Indonesian Criminal Code and Law Number 39 of 2014 concerning Plantations, as well as to examine the conformity of the return of cases by the police with the perspective of Fiqih Jinayah. This study used a normative juridical method by analyzing legal norms related to plantation product theft and the settlement of criminal cases. The results show that the application of legal rules to cases of plantation product theft in Jorong Kampung Pinang is in accordance with applicable norms, both in general criminal provisions and special provisions in the plantation sector, although its implementation still has several weaknesses that need to be improved. In addition, the return of cases by the police to the community for amicable settlement is in line with the concept of ta’zir in Islamic criminal law. The conclusion of the study emphasizes that the settlement of plantation product theft cases needs to consider the conformity between positive law and the principles of Fiqih Jinayah so that law enforcement continues to ensure justice, order, and the public good.